Children's Resilience to Not Working Before and During the Pandemic in Rural Indonesia - Hanafi, Zulfaning Tyas; Pramana, Setia (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2023)
Children are an asset to a country and a resource that will further national and international development goals. Children who work will be threatened by their health, safety, education, and development. In the last 10 years, BPS has recorded the percentage of child labor fluctuating with the latest record in 2021 at 2.63 percent. The high percentage makes the phenomenon of child labor still a global concern to be addressed as contained in the Sustainable Development Goals. Therefore, the purpose of this study is to determine the determinants of children's resilience not to work in rural areas during the observation period before and during the COVID-19 pandemic. This study uses a three-level survival analysis method by utilizing Sakernas data for August 2019-2020 and data from the BPS website. The results of this study obtained that the percentage of children aged 5-17 years who worked increased during the pandemic by 5.62 percent to 18.88 percent in rural areas. The variables of child gender, child education, child status at individual level; household head gender, household head occupation sector, and household poverty status at household level; and percentage of poor population at districts level significantly affect the resilience of children aged 5-17 not to work in the period before and during the COVID-19 pandemic.